Social representations of the motherhood of young women in Lima - Cieza Guevara, Kelly (2019)
The changes in society in recent decades and the growing participation of women in public space have impacted on the gender system and on women’s life projects. In this context, the article aims to identify and analyze motherhood representations among among young female university students from lower to middle strata of Lima and the meanings attributed to the construction of female identities.From a methodological framework based on the theory of the central nucleus and the development of interviews, we found that the young people interviewed plan their life projects based on factors such as motherhood and their professional development, but with new configurations. They try to integrate both of them, but tensions are generated, even though there is a greater appreciation of motherhood than of participation in the public space. Mainly, the young women interviewed consider that motherhood constitutes a source of affection and company. Additionally, motherhood is based on sacrifice, it is configured as the only space where women belong, it constitutes an idealization of the hegemonic family and it is a source of tensions between the domestic space and public space.